On the delta hedging related to the eigenvalues and the interest rate of the black-scholes equation - Kananthai A. (2017)
In this article, we study the delta hedging which is another way of minimizing the risk of investment. We can relate the delta hedging to the eigenvalues and the interest rate of the Black-Scholes equation. We found that such delta hedging depending on the relationship between the eigenvalues and the interest rate. We also found that the asymptotic form of the delta hedging related to the price of stock. Moreover, the results of this paper may not be useful in the real world application. But at least this paper may create the new results in the mathematical area which applying in the Financial Mathematics. © 2010 Academic Publications.